OP64 Economic Impact Of Cardiac Device Remote Monitoring In South Korea. (12th January 2018) - Ju, Kim Eung; Yoo, Justin; Colangelo, Irene; Morichelli, Loredana; Ricci, Renato Pietro; Ahn, Jeonghoon
Abstract : INTRODUCTION: The reduction of healthcare costs and societal cost due to remote monitoring (RM) of cardiac implantable electronic devices (CIEDs) has been demonstrated in several countries; however, to the best of our knowledge it does not exist for South Korea. This work aims at providing an estimation of the potential benefit of RM versus standard care (SC) of CIEDs in term of healthcare costs in South Korea, in order to provide additional substance to the currently ongoing societal debate about the value of telemedicine. METHODS: Healthcare resource consumption was taken from the results of the TARIFF study, a prospective, non-randomized, multicenter clinical trial designed in Italy to assess the economic benefits of RM follow-up in comparison with standard follow-up in 209 patients (107 SC, 102 RM). The main results demonstrated that RM reduced healthcare resource consumption by 54 percent from a healthcare services perspective (SC: EUR1, 044.89±1, 990.47 versus RM: EUR482.87±2488.10, p<.0001 (1). In order to perform a cost analysis from the perspective of the South Korean healthcare payer, the following unit costs were assigned to resources collected in TARIFF (hospitalizations, visits, examinations): fee-for-service tariffs, emergency tariffs and outpatient tariffs. Remote follow-up costs were considered as zero. RESULTS: From the perspective of the South Korean healthcare payer, the overall mean annual cost/patient in the RM group is 53 percent lower than in SC group (SC: EUR405, 439±40, 135 versus RM: EUR189, 96±725, 52, p<.0001) (SC: KRW 497, 145±49, 2137 versus RM: KRW 232, 936±890, 181, p<.0001). This is mainly due to a significant cost reduction in device-related hospitalizations, examination tests and visits in the follow-up period. CONCLUSIONS: RM of CIED patients is cost-saving from the perspective of the South Korean healthcare system. Introducing appropriate reimbursement for remote monitoring of CIED is not likely to change this result and should make RM sustainable for the provider and encourage widespread adoption of RM.